PENGARUH TRUSTWORTHINESS HOST SHOPEE LIVE SKINCARE SKINTIFIC OFFICIAL SHOP TERHADAP BRAND SWITCHING BEHAVIOR - Lulu Hasna Nabillah (2024)
Dissatisfaction with the previous skincare brand prompts consumers to switch brands, seek variety, and choose Skintific as an alternative. The host of Shopee Live Skintific serves as a trustworthy figure, boosting customer confidence, encouraging purchases, thereby altering the initial preferences for skincare products. This research aims to measure the influence the trustworthiness of the Shopee Live skincare Skintific Official Shop host has on brand switching behavior. This research uses the Theory of Planned Behavior and the Push-Pull Mooring Theory as grand theory. The author used an explanatory quantitative approach with a survey method distributed to Skintific Official Shop followers with a sample size of 124 respondents. The sampling technique used is the purposive sampling method. The results show that the trustworthiness variable of the Shopee Live skincare Skintific Official Shop host has influence of 55.4% on brand-switching behavior. The author hopes that further research can discuss other factors influenced brand-switching behavior in communication studies.